Forceps delivery--an outdated obstetric technique? - Parízek, A (Ceská gynekologie, 2010)
The use of forceps delivery has been at the height of obstetric methods for centuries. They have even been described as "royal", since from the time of their discovery they have helped solve even the most difficult delivery problems. In the past couple of decades, however, the use of alternative delivery tools, especially the vacuum extractor, have become more widespread during vaginal deliveries. The aim of this paper is to evaluate the current status of the use of forceps delivery and compare them with vacuum extraction, another tractive method. Published data, particularly from the Cochran database, are supplemented by personal experience.